2020
DOI: 10.35508/mkm.v2i2.2929
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Risiko Kejadian Gizi Kurang pada Anak Balita di Puskesmas Palla Kabupaten Sumba Barat Daya

Abstract: This study aims to analyze the factors associated with the risk of malnutrition in children under five at Palla Primary Health Care, Southwest Sumba District. The type of research was analytical observation with a case-control design. The sample of case and control consisted of 46 people per group. Data analysis was performed by calculating Odds Ratio (OR). The results showed that infectious diseases (OR= 2,590), mothers’ knowledge related to nutrition (OR=2,615), energy (OR= 2,067) and protein (OR=2,254) cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Infection and malnutrition are always closely related. Infections in malnourished children are mostly caused by impaired immune function, limited immune production and/or reduced functional capacity of all cellular components of the immune system in malnourished patients (Bili et al, 2020). c. Mother's knowledge about toddler nutrition is all forms of information owned by the mother regarding the nutrients needed for the toddler's body and the mother's ability to apply them in everyday life.…”
Section: Community Empowermentmentioning
confidence: 99%
“…Infection and malnutrition are always closely related. Infections in malnourished children are mostly caused by impaired immune function, limited immune production and/or reduced functional capacity of all cellular components of the immune system in malnourished patients (Bili et al, 2020). c. Mother's knowledge about toddler nutrition is all forms of information owned by the mother regarding the nutrients needed for the toddler's body and the mother's ability to apply them in everyday life.…”
Section: Community Empowermentmentioning
confidence: 99%
“…Selain itu, penelitian menunjukkan bahwa bayi dengan kekurangan konsumsi energi lebih cenderung mengalami kekurangan gizi dengan faktor 2,067 dibandingkan balita yang mengkonsumsi cukup energi. Salah satu faktor langsung yang dapat mempengaruhi status gizi balita adalah asupan gizi (Bili, Jutomo and Boeky, 2020).…”
Section: Pendahuluanunclassified
“…Malnutrition is still being one of the health problems in Indonesia. 1 Data from the basic health research in Indonesia in 2018 showed that the prevalence of malnutrition in toddler in Indonesia was 13,8%, while in Papua Province was 11,44%. Yapen Islands is one of the regencies in Papua Province with cases of malnutrition of 15.26% and is included in the top 10 highest cases in Papua Province.…”
Section: Introductionmentioning
confidence: 99%
“…5 Deficiency in energy consumption and protein consumption plays an important role as a risk factor for undernutrition in toddlers. 1 Lack of energy and protein intake in toddlers needs to be addressed by providing energy-and protein-dense additional food so that the nutritional needs of toddlers who experience malnutrition are fulfilled. 6 Providing additional food in the form of biscuits made from local food is one of the efforts that can be made to reduce nutritional problems in toddlers in Indonesia.…”
Section: Introductionmentioning
confidence: 99%